Ramp lesions: a systematic review of MRI diagnostic accuracy and treatment efficacy - Moreira, J (2020)
Purpose. We conducted a systematic review of the published literature to assess the accuracy of Magnetic Resonance Imaging (MRI) in establishing the presence of ramp lesions (RLs) in Anterior Cruciate Ligament (ACL) deficient knees and the clinical efficacy of the surgical repair of RLs. Methods. A comprehensive search of the MEDLINE, Web of Science and Scopus databases was performed according to PRISMA guidelines. Studies assessing MRI diagnostic accuracy for RLs or the clinical effect of RL repair in participants with ACL injuries were included. Diagnostic accuracy measures were pooled and plotted in forest plots. Preoperative and at last follow-up treatment efficacy outcome measures were extracted and plotted in forest plots, for graphical comprehension. Results. Sixteen studies met the criteria and were included. The diagnostic analysis showed a pooled sensitivity, specificity, positive and negative likelihood ratios of 65.1% (95% CI, 59.73 to 70.42), 91.6% (95% CI, 89.14 to 94.05), 2.91 (95% CI, 2.38–3.55) and 0.53 (95% CI, 0.44–0.64), respectively, with high heterogeneity (I2 above 80%) for all measures. Treatment analysis showed improved Lysholm Knee Score, IKDC score and laxity difference between the knees in all studies after meniscal suture repair. A separate analysis showed no differences between repair of smaller, stable, RLs with meniscal sutures and repair with abrasion and trephination only. Conclusion. Although the results present considerable heterogeneity, MRI seems to demonstrate moderate accuracy in the diagnosis of RLs in patients with ACL tear and the surgical repair of RLs can be associated with improved overall outcomes.